Exposure to cyanide following a meal of cassava food - Oluwole, O.S.; Onabolu, A.O.; Sowunmi, A. (Elsevier, 2002)
Exposure to cyanide from gari, a popular cassava food in West Africa, is implicated in the causation of ataxic polyneuropathy and amblyopia, but this has been questioned because cyanide was not detected in gari in a study. This study was carried out to determine if gari is a source of exposure to cyanide. Gari (150 g) containing cyanohydrin, from which 128 μmol of cyanide ions could be released, was dissolved in 500 ml of cold water for each of the 12 healthy subjects to drink. Concentrations of cyanide in plasma and erythrocytes were determined at baseline and following the meal at 30 min, 1 h, hourly for 4 h and two hourly for 12 h. The mean concentrations of cyanide in the plasma were 6 μmol/l (95% CI 2–10) at baseline, 12 μmol/l (95% CI 6–17) at peak and 6 μmol/l (95% CI 2–10) on return to baseline. The mean amount of cyanide absorbed into the plasma was 13 μmol (S.D. 12), while the transit time of absorbed cyanide was 7.3 h (S.D. 2.1). This study shows that exposure to cyanide follows consumption of gari, but the amount of cyanide absorbed into the plasma from a single meal is small and unlikely to cause acute intoxication. The long transit time of absorbed cyanide in the plasma suggests that frequent intake of gari could cause cyanide to accumulate in the plasma.